Answer:
See the attached file for the answers.
Step-by-step explanation:
See the attached file for the explanation
Answer:
f(-2) = -1
Step-by-step explanation:
One way of doing this is to substitute -2 for x in every place where x shows up:
f(x) = 4x + 3x^2 − 5 → f(-2) = 4(-2) + 3(-2)^2 − 5
→ f(-2) = -8 + 3(4) - 5, or f(-2) = 4 - 5, or f(-2) = -1
Answer:
the same as multiplying them, except you're doing the opposite: subtracting where you would have added and dividing where you would have multiplied. If the bases are the same, subtract the exponents. Remember to flip the exponent and make it positive, if needed.
Step-by-step explanation:
The only 'small number' that I know that would affect the answer is an exponent that looks like ³ so the problem would be x³+x
remember that x³=x times x times x
if x=3 then
3³+3=27+3=30
Answer:
option (a) is correct.
2 + m - 1 + m is an equivalent expression to the given expression 3m+1-m
Step-by-step explanation:
Given expression 3m+1-m
We have to choose an equivalent expression from given options.
Equivalent expression are those expression that looks different but are same.
Like 4+2 = 6 and 3+ 3 = 6
Both have same value but looks differently.
Like terms are term having same variable with same degree.
Consider the given expression 3m+1-m
Simplify by adding like terms,
3m + 1 - m = (3-1) m + 1
Thus, (3-1) m + 1 = 2m + 1
Also 2m + 1 can be written as m + m + 2 - 1
Thus, option (a) is correct.